2007
DOI: 10.1677/erc-07-0021
|View full text |Cite
|
Sign up to set email alerts
|

Parafibromin immunoreactivity: its use as an additional diagnostic marker for parathyroid tumor classification

Abstract: Parafibromin is a protein product derived from the hyperparathyroidism 2(HRPT2) tumor suppressor gene and its inactivation has been coupled to familial and sporadic forms of parathyroid malignancy. In this study, we have conducted immunohistochemistry on 33 parathyroid carcinomas (22 unequivocal and 11 equivocal) using four parafibromin antibodies directed to different parts of the protein.Furthermore, for a fraction of cases, the immunohistochemical results were compared with known HRPT2 mutational status. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 33 publications
5
99
1
7
Order By: Relevance
“…Similar results have been reported by other workers. 59,60 However, in our own experience, loss of parafibromin staining has been observed in some adenomas unassociated with the HPT-JT syndrome, whereas some PT-CAs have been positive. 61 On the basis of a detailed literature review, 46% of PT-CAs have been reported as parafibromin negative, whereas 88% of cases have been reported as negative and/or weakly positive.…”
Section: Parathyroid Carcinomamentioning
confidence: 62%
“…Similar results have been reported by other workers. 59,60 However, in our own experience, loss of parafibromin staining has been observed in some adenomas unassociated with the HPT-JT syndrome, whereas some PT-CAs have been positive. 61 On the basis of a detailed literature review, 46% of PT-CAs have been reported as parafibromin negative, whereas 88% of cases have been reported as negative and/or weakly positive.…”
Section: Parathyroid Carcinomamentioning
confidence: 62%
“…28 A recent study found that 68% (15 of 22) of unequivocal parathyroid carcinomas showed reduced expression of parafibromin in contrast to the positive parafibromin staining of all 25 parathyroid adenomas used as control. 35 The authors 35 concluded that parafibromin immunostaining was a useful additional marker. They also found that benign tumors stained positive, whereas reduced expression could indicate malignancy or rare cases of adenomas, possibly with HRPT2 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…These new markers include parafibromin, expression of Rb, Ki-67 and Galectin-3. Unfortunately, none of these has enough sensitivity and specificity on its own, therefore their results need to be interpret the results jointly [3,16].…”
Section: C4mentioning
confidence: 99%